Central Pontine Myelinolysis Presenting With Tremor in a Child With Celiac Disease. (March 2014) - Sharma, Preeti; Sharma, Suvasini; Panwar, Neha; Mahto, Deonath; Kumar, Praveen; Kumar, Atin; Aneja, Satinder
A 4-year-old boy presented with a history of tremor for 7 days. He also had recurrent diarrhea for the previous 1 year, and poor weight gain. Magnetic resonance of the brain was suggestive of central pontine myelinolysis. There was no evidence of electrolyte abnormalities. The serum tissue transglutaminase level was markedly elevated, and the duodenal biopsy revealed features of celiac disease. The patient was started on gluten-free diet. The tremor resolved within 3 months. Repeat imaging of the brain done 3 months after starting gluten-free diet showed complete resolution of the lesion. This case highlights the unusual presentation of central pontine myelinosis as tremor in a malnourished child with celiac disease.